Gut Microbiota Was Involved in the Process of Liver Injury During Intra-Abdominal Hypertension - Zhao, Zeyu; Guo, Zhengchang; Yin, Zhengliang; Qiu, Yue; Zhou, Bo (Frontiers in Physiology, 2021)
Background: Intestinal damage caused by intra-abdominal hypertension (IAH) and abdominal compartment syndrome (ACS) can lead to the ectopic gut microbiota, which can contribute to liver injury via portal veins. Therefore, it is speculated that gut microbiota disorder caused by IAH/ACS may result in liver injury. The relationship between gut microbiota and IAH/ACS-related liver injury was investigated in this study. Methods: A model of IAH was established in rats, and 16S rRNA sequencing was analyzed for gut microbiota in the feces of rats. The elimination of gut microbiota was completed by antibiotics gavage, and fecal microbiota transplantation (FMT) was used to change the composition of gut microbiota in rats. Results: In addition to the traditional cause of liver blood vessel compression, liver injury caused by IAH was also associated with gut microbiota dysbiosis. Gut microbiota clearance can relieve liver injury caused by IAH, while FMT from IAH-intervened rats can aggravate IAH-related liver injury. Conclusion: The gut microbiota was one of the most important factors contributing to the IAH-related liver injury, and the JNK/p38 signaling pathway was activated in this process.